Comparative Analysis of Haemagglutination Inhibition Antibody Production Against Three Lentogenic Newcastle Disease Virus Vaccines in Broiler Chicks (Bangladesh Journal of Microbiology, 2012)
The comparative analysis of haemagglutination Inhibitation (HI)-antibody production against three lentogenic  Newcastle disease virus vaccines BCRDV (F-strain), Izovac B1 Hitchner ® (B1 strain) and Cevac New L® (LaSota strain) was analyzed in broiler chicks. For this, three groups A, B and C, each consisted of 30 birds  were vaccinated with single dosage at day 9 and the other group of 10 birds was maintained as unvaccinated  control. Sera samples obtained randomly from 10 birds of each group on the day 17, 20, 28 and 32 and the HI  titers estimated. Maternally derived antibody persisted to a maximum level of 17 day and than declined to  minimum or none. The results revealed that vaccination of young birds with locally produced BCRDV by the  Department of Livestock Service elevated HI antibody at comparable level with that of commercially available  vaccine Izovac B1 Hitchner and Cevac New L®. The F value preformed with mean±SD of 17, 20, 28 and 32  days appeared non significant among the HI titers of the birds vaccinated with BCRDV, Izovac B1 Hitchner® (B1 strain) and Cevac New L®. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11808 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 41-43